Cognitive performance and lifetime cannabis use in patients with first-episode schizophrenia spectrum disorder - Hájková, M; Knížková, K; Siroňová, A; Keřková, B; Jonáš, J; Šustová, P; Dorazilová, A; Rodriguez, M (Cognitive neuropsychiatry, 2021)
INTRODUCTION: Cognitive impairment is among the core features of schizophrenia. In a healthy population, the cognitive deficit is often linked with cannabis abuse, and although the same would be expected in patients with schizophrenia, research has presented contradictory results. METHODS: Participants were patients with first-episode schizophrenia (FES) spectrum disorder who had been lifetime cannabis users (N = 30), FES non-users (N = 53) as well as healthy controls (HC) also divided into cannabis users (N = 20) and non-users (N = 49). All participants underwent an extensive neurocognitive assessment and filled in a cannabis questionnaire, which allowed for a comparison of the four groups on cognitive functioning. RESULTS: FES patients using cannabis showed less impaired cognitive functioning with the most prominent difference in visual memory compared to FES non-users. However, they differed neither in the clinical assessment of general psychopathology, positive and negative symptoms, nor in medication from the patient's non-users. A comparison of the HC who used cannabis, and those who did not, revealed no sizeable differences in cognitive performance between the groups. CONCLUSIONS: The results delivered supporting evidence for the trend of superior neurocognitive performance in FES patients with a lifetime history of cannabis use compared to non-using patients.
Keywords: Cannabis; schizofrenie; substance use; Cognition Disorders; kognitivní poruchy; Humans; cannabis; psychosis; abúzus marihuany; lidé; Cognition; Schizophrenia; cognition; kognice; Marijuana Abuse